REGIONAL DENSITIES OF RETINAL CAPILLARIES AND RETINAL SENSITIVITIES AFTER MACULAR HOLE SURGERY WITH INTERNAL LIMITING MEMBRANE PEELING. Issue 8 (August 2020) - Baba, Takayuki; Kakisu, Masato; Nizawa, Tomohiro; Oshitari, Toshiyuki; Yamamoto, Shuichi
Abstract : Purpose: To measure the vascular density (VD) of the retinal capillary plexuses by optical coherence tomography angiography (OCTA) after surgery for an idiopathic macular hole. Methods: Retrospective, observational case series.Sixteen eyes of 16 patients with an idiopathic macular hole underwent vitrectomy with internal limiting membrane peeling. The VDs of the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were determined by OCTA, and the retinal sensitivity (RS) and the inner retinal thickness (IRT) were measured before, and at 3, 6, and 12 months after the surgery. The VD, RS, and IRT were measured at the four parafoveal quadrants. Results: The mean age was 68.9 years. The VDs of the SCP and DCP were significantly correlated with the RS and IRT at 12 months postoperatively (all P < 0.001 for both SCP and DCP). The VDs of the SCP and DCP were higher, the RS more sensitive, and the IRT thicker in the nasal than the temporal quadrant at 12 months ( P < 0.001, <0.001, =0.009, <0.001, respectively). Conclusion: The significant correlation between the VDs of the SCP and DCP and the RS and IRT may be due to the nasal shift of the posterior retina. Abstract : The vascular densities of the superficial and deep capillary plexuses measured by optical coherence tomography angiography were significantly correlated with the retinal sensitivity after vitrectomy for an idiopathic macular hole. The vascular densities and sensitivity were significantly higher in the nasal than in the temporal quadrants at 12 months.